UNDERSTANDING THE KEY FACTORS THAT IMPACT THE QUALITY OF PARTNERSHIP RELATIONS (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
The objective of this paper is to comprehensively examine partnership relations and analyze the key factors that affect their quality. The study will focus on identifying individual factors that significantly contribute to the quality of interpersonal relationships among romantic partners. Additionally, the paper will provide a clear definition of partnership relationships, outlining their fundamental characteristics and features. By highlighting the critical factors influencing partnership relations, this study aims to enhance our understanding of the dynamics that drivehealthy and sustainable romantic relationships.We will be presenting the findings from a survey "Quality of Partnership Relations," which was conducted with 72 respondents aged from 17 to 73. This survey aimed to gather insights into participants' individual experiences, opinions, and understandings regarding the quality of partnership relations. The results of this research will complement the theoretical elaboration presented.We will compare the results obtained from this survey with data extracted from professional literature and other research, for each individual factor. Our objective is to identify similarities and differences between the findings from the literature and the real-life experiences of the survey respondents. By doing so, we hope to gain deeper insights into the factors that impact the quality of partnership relations.The underlying hypothesis posits that the quality of a partner relationship is significantly influenced by interpersonal factors. In other words, the way individuals interact and communicate with each other is paramount in determining the success and satisfaction of their relationship.